2017
DOI: 10.1111/1750-3841.13923
|View full text |Cite
|
Sign up to set email alerts
|

Production, Characterization, and Stability of Orange or Eucalyptus Essential Oil/β‐Cyclodextrin Inclusion Complex

Abstract: The aim of this study was to produce and characterize inclusion complexes (IC) between β-cyclodextrin (β-CD) and orange essential oil (OEO) or eucalyptus essential oil (EEO), and to compare these with their pure compounds and physical mixtures. The samples were evaluated by chemical composition, morphology, thermal stability, and volatile compounds by static headspace-gas chromatography (SH-GC). Comparing the free essential oil and physical mixture with the inclusion complex, of both essential oils (OEO and EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 39 publications
0
55
0
1
Order By: Relevance
“…The results of Kringel et al. () also suggested that CD inclusion complexes could efficiently and stably encapsulate guest molecules even at high temperatures due to the ability of the β‐CD to efficiently retain essential oils to prevent their evaporation.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The results of Kringel et al. () also suggested that CD inclusion complexes could efficiently and stably encapsulate guest molecules even at high temperatures due to the ability of the β‐CD to efficiently retain essential oils to prevent their evaporation.…”
Section: Resultsmentioning
confidence: 98%
“…Preparation of the inclusion complex: EEO inclusion complex (β‐CD‐EEO) was performed according to a method described in the published literature (Kringel et al., ; Xiang, Zhang, Li, & Li, ). β‐CD (3.5 g) was dissolved in 100 mL of distilled water maintained at 40 °C in a constant temperature heating stirrer, and then 2.0 mL of an essential oil and ethanol mixture (1:1 V/V) was slowly added to the β‐CD solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peels of Valencia oranges were frozen and crushed to increase the extraction yield. The essential oil was obtained by a hydro‐distillation technique using a Clevenger apparatus in accordance with the method described by Kringel et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The β‐CD/OEO inclusion complex was prepared by the precipitation method as described by Kringel et al ().…”
Section: Methodsmentioning
confidence: 99%